A rare case of yolk sac tumor of the vagina: Cytology and histopathological findings - Pant, Anil Dev; Sayami, Geeta; Prasad, Viswanath; Shrestha, Anjan (Nepal Journal of Obstetrics and Gynaecology, 2009)
Yolk sac tumors, the most common germ cell tumor in young infants and children, however, are distinctly uncommon site in the vagina. A baby with bleeding per vaginum since one month presented at 9 months of age with raised Serum α- fetoprotein (AFP) but normal levels of ß-HCG and CA-125 is reported. Fine needle aspiration from the mass yielded material suggestive of a germ cell tumor. The histopathological findings further confirmed the diagnosis of a yolk sac tumor. Key words: yolk sac tumor, endodermal sinus tumor, pediatric, vagina, germ cell tumor, α-fetoprotein (AFP) doi:10.3126/njog.v1i2.2402 N. J. Obstet. Gynaecol Vol. 1, No. 2, p. 63-65 Nov-Dec 2006